Influence of institutional and moral orientations on relational risk management in supply chains. Issue 2 (June 2016) - Cheng, Jao-Hong; Chen, Mu-Chung
Abstract: Inter-organizational relationships in supply chains are built, maintained, and enhanced to achieve corporate goals. However, relational risk will weaken the success of supply chains. Manufacturers must build forms of relational governance to safeguard against the relational risk of partners. For managing relational risk, this research investigates the contribution of institutional and moral orientations to relational risk management. The results of the study of 260 major manufacturing firms in Taiwan suggest that three types of relational risk—opportunistic behavior, loss of competences, and incomprehension—are significantly affected by institutional and/or moral orientations. The findings provide useful insights into how supply chain members should reinforce their institutional and moral views of relational governance and manage relational risks faced by the supply chain as a whole. Highlights: This paper contributes to manage three types of relational risk in supply chains. Relational risk improvement is affected by institutional and moral orientations. Institutional and moral orientations restrain the encroachment of relational risk.